Social Media for Government: Theory and Practice - Brittany L Bowman (Journal of Applied Communications, 2019)
Book review of Social Media for Government: Theory and Practice, by Staci M. Zavattaro and Thomas A. Bryer
Keywords: social media; book review; digital marketing; public relations; government